"Green Electrodes" Modified with Au Nanoparticles Synthesized in Glycerol, as Electrochemical Nitrite Sensor. Issue 8 (4th May 2015) - Gobelli, Dino; Mariano Correa, N.; Fátima Barroso, M.; Moyano, Fernando; Molina, Patricia G.
Abstract A new environmentally friendly Au nanoparticles (Au NPs) synthesis in glycerol by using ultraviolet irradiation and without extra‐added stabilizers is described. The synthesis proposed in this work may impact on the non‐polluting production of noble nanoparticles with simple chemicals normally found in standard laboratories. These Au NPs were used to modify a carbon paste electrode (CPE) without having to separate them from the reaction medium. This green electrode was used as an electrochemical sensor for the nitrite detection in water. At the optimum conditions the green sensor presented a linear response in the 2.0×10−7–1.5×10−5 M concentration range, a good detection sensitivity (0.268 A L mol−1), and a low detection limit of 2.0×10−7 M of nitrite. The proposed modified green CPE was used to determine nitrite in tap water samples.